Development of a Methodology for the Determination of Pesticide Residues in Cajá-Manga Pulp (Spondias dulcis L.) Using Solid-Liquid Extraction with Low-Temperature Partitioning - Escarlet T. D. Santana; Dayane F. Soares; Anizio M. Faria (Journal of Chemistry)
Emergent fruits with functional properties and sui generis flavours are increasingly gaining international market, mainly due to the pleasant taste and its nutritional properties. However, methodologies for determination of pesticide residues in these fruits are still incipient or nonexistent. In this work, a simple, rapid, and accessible methodology to small laboratories was developed, optimized, and validated for the determination of four pesticide residues in the cajá-manga pulp: chlorpyrifos, thiabendazole, carboxin, and difenoconazole. The extraction of pesticides from the cajá-manga pulp was performed by the liquid-solid extraction with low-temperature partitioning, achieving efficiency in the range of 75.3–129.3% with limits of quantification between 170 and 430 ng·g−1 for all compounds. The methodology was validated according to the SANTE/11813/2017 document, demonstrating good detectability, selectivity, precision, and accuracy with limits of quantification within the range of the maximum residual limits preconized for the compounds. The quantification was performed by gas chromatography with flame ionization detection which, although it does not present the best detectability for the compounds, is a lower cost instrumentation and is available in several analysis laboratories in Brazil, making the method more accessible to evaluate the pesticide residues in fruit pulp. Thus, in this work, a methodology for the determination of pesticides in the cajá-manga pulp is available for the monitoring of pesticide residues in fruit pulp, in an efficient and accessible way.